Lipid metabolism in children and adolescents: Impact on vascular biology - Mietus-Snyder, Michele; Krauss, Ronald M. (Journal of clinical lipidology, 2008)
Age remains one of the strongest risk factors for atherosclerotic disease, but the protection conferred by youth can be eroded by cardiovascular risk factors such as dyslipidemia. Elevated atherogenic lipoproteins and inadequate reverse cholesterol transport contribute to an inflammatory response in the vascular wall that promotes atheroma formation. The focus of this review is on the hepatic lipid triage that determines the balance of atherogenic and atheroprotective lipoproteins. Under the continuous influence of energy intake, level of insulin sensitivity, and circulating free fatty acids, the dynamic hepatic processing of lipoproteins is subject to global metabolic transcriptional regulation by the family of lipid-sensing peroxisome proliferator-activated receptors. The endogenous activation of gene networks under the control of these receptors may play an underappreciated role in maintaining vascular health in children by mediating energy metabolism, lipid storage, and transport, as well as innate immunity. Multiple independent lines of evidence suggest that the progressive dyslipidemia, insulin resistance, vascular dysfunction, and cardiovascular risk associated with age can be either delayed or accelerated as a function of lifestyle choices that either activate or repress these central transcriptional regulators. The implications for pediatric lipid metabolism and vascular biology are considerable.